KENAIKAN TARIF DASAR LISTRIK DAN RESPON KEBIJAKAN UNTUK MEMINIMISASI DAMPAK NEGATIF TERHADAP PEREKONOMIAN - Tri Isdinarmiati; Rina Oktaviani (IPB University, 2012)
Electricity is one of the strategic commodities in Indonesia. The Increasing of electrical price (so called TDL stand for Tarif Dasar Listrik) administered by the government will be negative impact on Indonesian economic performance. Based on this research analysis, a rise of TDL will have negative impact on macro and sectoral economic performance. This study aims to analyze the effects of a rise of TDL and policy responses to minimize its negative impacts on Indonesian economic performance. The data which is used in this research areInput Output Table, Social Accounting Matrix (SAM) and SUSENAS data. Sources of data obtained from Board Central of Statistics. The analysis using Computable General Equilibrium (CGE) model is called INDOTDL CGE model. The simulation results show that a rise of TDL will have negative impact oneconomic growth, household consumption, export, employment and sectoral demand. This study also shows that an increase of efficiency in electricity sector by 10 percent is expected to decrease the electrical price. In addition, a rise of TDL which is followed by an increase of efficiency or decrease of value added tax (VAT) policy in all sector have positive impact on macro and sectoral economic performance on Indonesian. The most effective policy to economic improvementis to increase efficiency of electricity sector, so TDL doesn’t need to be increased.Keywords : TDL, CGE, Efficiency, VAT, Economic Performance